Relación entre los programas alimentarios de la municipalidad provincial y la anemia en niños de 6 a 59 meses en Maynas 2016-2023 - Bardales Lopez, Karoline (2025)
Childhood anemia is a social problem that negatively affects the cognitive and physical development of the child. Likewise, public spending on food programs is presented as a tool that could promote the reduction of anemia in vulnerable populations. In this sense, the research aims to determine the relationship between the execution of public spending in the food programs of the Provincial Municipality and the prevalence of anemia in children from 6 to 59 months of Maynas during the period 2016-2023. The study is developed through the quantitative type, correlational level and non-experimental design with longitudinal data. The research determined a growing behavior of public spending on food programs, going from S/ 4,962,907 in 2016 to S/ 8,603,990 in 2023. Likewise, the prevalence of anemia shows alarming levels given that an average of 43.74% was identified during the period studied. No significant relationship was found between the execution of public spending in the Food Programs of the Provincial Municipality of Maynas and the prevalence of anemia in children from 6 to 59 months of age in Maynas, or in Iquitos.